2003
DOI: 10.1034/j.1600-0412.2003.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase‐8 correlates with the cervical ripening process in humans

Abstract: The results indicate that MMP-8 is involved in the process of cervical ripening, and that MMP-1 and -3 and their inhibitors TIMP-1 and -2 may also play a role in this complicated process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 38 publications
(47 reference statements)
4
46
0
Order By: Relevance
“…The dramatic ripening of the cervix involves a cascade of MMPs that includes MMP-8 (collagenase-2), MMP-3 (stromelysin), and gelatinases (MMP-2 and -9). Indeed, high levels of MMP-8 (Sennström et al, 2003) and MMP-2 and -9 (Stygar et al, 2002) have been observed in the stromal tissue of ripened cervix in women at parturition, and MMP-3 has been detected in rat cervix, also at parturition (Chien et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The dramatic ripening of the cervix involves a cascade of MMPs that includes MMP-8 (collagenase-2), MMP-3 (stromelysin), and gelatinases (MMP-2 and -9). Indeed, high levels of MMP-8 (Sennström et al, 2003) and MMP-2 and -9 (Stygar et al, 2002) have been observed in the stromal tissue of ripened cervix in women at parturition, and MMP-3 has been detected in rat cervix, also at parturition (Chien et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…The influx of inflammatory cells coincides with a rise in the levels of matrix metalloproteinases (MMP) -1, -13, and -8 that degrade fibrillar collagen, and MMP-9 that degrades basement membranes (Aronsson et al, 2005;Rath et al, 1998;Sennström et al, 2003). MMP-8, also known as neutrophil collagenase-2, preferentially cleaves type I collagen (Balbín et al, 1998;Libert, 2006;Maymon et al, 2000;Sennström et al, 2003;Van Lint and Sulkala et al, 2007).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Nitric oxide (NO) may be involved in the process of cervical ripening and may cause the inflammatory-like changes inducing arterial dilation, leakage of fluid to the extracellular matrix, and leukocyte infiltration [15]. Nitric oxide may also regulate the activity of the metalloproteinases and induce prostaglandin production by stimulating cyclooxygenase activity [16].…”
Section: Discussionmentioning
confidence: 99%